The Control of Reactive Oxygen Species Influences Porcine Oocyte In Vitro Maturation. Issue 2 (17th December 2014) - Alvarez, GM; Morado, SA; Soto, MP; Dalvit, GC; Cetica, PD
Contents The aim of this study was to examine the effect of varying intracellular reactive oxygen species (ROS) levels during oocyte in vitro maturation with enzymatic ROS production systems (xanthine + xanthine oxidase or xanthine + xanthine oxidase + catalase), scavenger systems (catalase or superoxide dismutase + catalase) or cysteine on porcine oocyte maturation. Oocyte ROS levels showed an increase when H2O2 or O2∙‐ production systems were added to the culture medium (p < 0.05). On the other hand, the presence of ROS scavengers in the maturation medium did not modify oocyte ROS levels compared with the control after 48 h of maturation, but the addition of cysteine induced a decrease in oocyte ROS levels (p < 0.05). The ROS production systems used in this work did not modified the percentage of oocyte nuclear maturation, but increased the decondensation of sperm head (p < 0.05) and decreased the pronuclear formation (p < 0.05). In turn, the addition of O2∙‐ and H2O2 scavenging systems during in vitro maturation did not modify the percentage of oocytes reaching metaphase II nor the oocytes with decondensed sperm head or pronuclei after fertilization. However, both parameters increased in the presence of cysteine (p < 0.05). The exogenous generation of O2∙‐ and H2O2 during oocyte in vitro maturation would not affect nuclear maturation or later sperm penetration, but most of the spermatozoa cannot progress to form the pronuclei after fusion with the oocyte. The decrease in endogenous ROS levels by the addition of cysteine would improve pronuclear formation after sperm penetration.